Unnatural Chiral N-tert-Butanesulfinyl α-Amino Acid Synthesis; A General Synthetic Strategy to N-Boc-Phenylalanine Analogue Alternatives - Lin, Li; Fu, Xu; Ma, Xiaojuan; Zhang, Jinlong; Wang, Rui (Synlett, 2012)
This work provides a general approach to unnatural chiral N-tert-butanesulfinyl α-amino acid synthesis with high yields and excellent diastereoselectivities (dr up to 98:2). The asymmetric addition of organometallic reagents to N-tert-butylsulfinyl imino acetate proceeded with excellent diastereo- and regioselectivities even on a 10 mmol scale. The sterically constrained 2′,6′-dimethyltyrosine (Dmt) derivative was also readily prepared from commercially available and inexpensive starting materials through simple steps.
Keywords: unnatural α-amino acids; peptides; regioselectivity; asymmetric synthesis; chiral auxiliaries